Consumption expenditure on processed meat and its correlates: an ethnic comparison - Yong, Kang Cheah; Appannah, Geeta; Abdul Adzis, Azira (Taylor Francis, 2022)
Background: The objective of the present study is to investigate the influences of sociodemographic and household factors on consumption expenditure on processed meat among households in Malaysia.